Jatropha Cultivation and Development of Model Biofuel Park in Malwa plateau region - Singh, Umesh (Indian Farming, 2018)
A Project Site of Defence Institute of Bio-Energy Research (DIBER), Haldwani (Uttarakhand), one of the constituent institutes of the Defence Research and Development Organization (DRDO), was started in 100 hectares land of Military Farm, Mhow (Madhya Pradesh) under DRDO-Army Biodiesel Programme since April 2007. Establishment of a Biofuel Park by cultivating Jatropha plants was also among one of the prime objectives of the programme.